2017
DOI: 10.1055/s-0037-1604489
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Artery Doppler Velocimetry of Uterine Leiomyomas in Nigerian Women

Abstract: Objective To describe the blood flow velocities and impedance indices changes in the uterine arteries of leiomyomatous uteri using Doppler sonography. Methods This was a prospective, case-control study conducted on 140 premenopausal women with sonographic diagnosis of uterine leiomyoma and 140 premenopausal controls without leiomyomas. Pelvic sonography was performed to diagnose and characterize the leiomyomas. The hemodynamics of the ascending branches of both main uterine arteries was assessed by Doppler int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
(58 reference statements)
1
5
1
Order By: Relevance
“…Furthermore, the perifibroid and intrafibroid Doppler indices did not differ significantly with presence or absence of symptomatology generally and menorrhagia specifically. This is in contrast to previous report [ 26 ] of significantly higher PSV, EDV, TAMX in the main uterine artery of symptomatic subjects as well as higher main uterine artery flow velocities and lower resistance to flow in those with menorrhagia. Furthermore, Sladkevicius et al [ 31 ] reported “much higher TAMX values from the arteries supplying the large myomas of the symptomatic premenopausal women than from those supplying the small myomas of the asymptomatic postmenopausal women.” However, we are of the opinion that the documented elevated TAMX by Sladkevicius and co-workers [ 31 ] is more likely due to the difference in the myoma sizes of the 2 groups.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the perifibroid and intrafibroid Doppler indices did not differ significantly with presence or absence of symptomatology generally and menorrhagia specifically. This is in contrast to previous report [ 26 ] of significantly higher PSV, EDV, TAMX in the main uterine artery of symptomatic subjects as well as higher main uterine artery flow velocities and lower resistance to flow in those with menorrhagia. Furthermore, Sladkevicius et al [ 31 ] reported “much higher TAMX values from the arteries supplying the large myomas of the symptomatic premenopausal women than from those supplying the small myomas of the asymptomatic postmenopausal women.” However, we are of the opinion that the documented elevated TAMX by Sladkevicius and co-workers [ 31 ] is more likely due to the difference in the myoma sizes of the 2 groups.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, a possible contribution to this Doppler picture from healing by fibrosis, if any, is uncertain but plausible. These intrafibroid artery Doppler differences between post-myomectomy subjects and those without previous myomectomy were not observed in the main uterine artery as we reported previously [ 26 ] or in the perifibroid artery of this study.…”
Section: Discussionsupporting
confidence: 82%
“…Measurement of fibroid growth rates has an important role in the development of tumor-inhibiting treatment modalities for perimenopausal women. Unlike Doppler USG, MRI remains as an expensive imaging tool that requires more resources (15). Previously, findings from some other studies have confirmed the general evidence for the reliability of Doppler USG when performed by experienced and skilled sonographers (16 -22).…”
Section: Discussionmentioning
confidence: 58%
“…With their descending cervical and ascending uterine branches, the arcuate arteries can be visualized in the outer myometrium, often close to the uterine border. Doppler waveforms of uterine artery typically present a high-velocity, high-resistance pattern, and an identifiable dicrotic notch (Bhatt et al, 2006;Idowu et al, 2017;Secil et al, 2008).…”
Section: Acquisition Techniquementioning
confidence: 99%